INVESTIGATING THE SYNTHESIS OF NMC AND LCO THIN-FILM CATHODES FOR ENHANCED PERFORMANCE IN LITHIUM-ION BATTERIES - Kabashev, Zhaksylyk (School of Engineering and Digital Sciences, 2023)
Thin-film lithium batteries are designed to improve the longevity, storage capacity, energy density, and safety level of lithium batteries. The materials of the thin-film of electrodes should fit several criteria, such as ionic conductivity, electrochemical stability, and optimized solid electrolyte characteristics. This study investigated the electrochemical performance of an NMC-based lithiumion battery, with a focus on understanding the voltage-capacity relationship and cycling performance. The obtained experimental results showed a peak voltage of 3.1 V, which is considerably lower than the expected value of 4.2 V for NMC-based cells. Additionally, the specific capacity was found to be 2.09 μAh/g, which is significantly lower than the reported capacities in the literature for similar battery chemistries. The deviation from the expected performance suggests potential issues in the materials, cell design, or experimental conditions. Despite the suboptimal performance, this study provides valuable insights into the challenges associated with NMC-based lithium-ion batteries and serves as a foundation for further investigations and optimizations. Future work should focus on identifying the factors contributing to the observed performance and exploring strategies to enhance the electrochemical behavior of NMC-based cells to make them suitable for various applications, such as electric vehicles and energy storage systems.
Keywords: Type of access: Open Access; NMC electrode; magnetron sputter deposition; lithium ion battery; coin cell; charge-discharge cycle